Guinea-Bissau : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Guinea-Bissau. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the 2007 Article IV Consultation on Guinea-Bissau highlights post-conflict challenges and recent economic developments. The conflict and ensuing political instability have taken a toll on growth and economic policies, and most macroeconomic indicators have worsened in the post-conflict period. The frequent changes in government have eroded international support. The recently appointed government has adopted an emergency program to address the main sources of fiscal slippages that have gained broad support both domestically and internationally, but significant donor support is still needed to fill the financing gap.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet